Capacidades empreendedoras e inovativas dos agricultores para a sustentabilidade doas pequenas propriedades rurais familiares: um estudo multicaso em Rondinha, no Rio Grande do Sul, 2017 - Potrich, Rafaele (2017)
The entrepreneurial and innovative capacities of family farmers is a contemporary theme in the field of Brazilian organizational studies (ORS), as well as in research on entrepreneurship and small farm management. In the present dissertation, we question how the entrepreneurial and innovative capacities of family farmers can contribute to the sustainability of small family farms. The objective was to understand the contribution of individual capacities of family farmers to the sustainability of small family farms. Specifically, the research space was characterized, investigated and described the productive, family and social dynamics of small family farms. The processes of production and marketing of rural products were also analyzed, considering the three-dimensional sustainability of these properties and, finally, the entrepreneurial and innovative capacities of family farmers were identified. The theoretical assumption is that the capabilities studied in the field of strategy at the organizational level fall within the area of cognition and behavioral science at the level of the individual and open space to study individual capacities of family farmers. The reference of the theory of capacities is that it guides the study, based on the family farming understood as the small family rural property composed of social subjects identified as family farmers. The research was developed at the descriptive level by the strategy multiple case study and qualitative approach of the data. The research area consisted of small rural properties located in the municipality of Rondinha, in the state of Rio Grande do Sul. Data sources were three rural families residing in small rural properties, selected according to the criteria defined by Emater / RS-Ascar for considered sustainable. The subjects of the survey were the owners of small rural farms, called "family farmers", and members of their family, as well as technicians from Emater/RS-Ascar Rondinha, President of the Rondinha Farm Workers' Union and Mayor of Rondinha. The data were collected through interview, observation and documentary analysis. Data analysis was compiled by the categorical analysis of the content analysis method. The results indicate that family farmers have entrepreneurial and innovative capacities, which are determinant in the management of small rural properties, whose demands refer to family dynamics, production and marketing. The individual capacities described serve as a theoretical contribution to discuss the sustainability of small family farms. In the context of the new rurality, it is important not only to study the variables that form the triple botton line (TBL) of sustainability, that is, the economic, financial and environmental dimensions, but the individual capacities of family farmers. Small family farms are reproductive environments for the quality of life and wellbeingof members of the rural family and their sustainability depends on individual capacities. The family farmer is a decision maker, an active subject in the social relations of the territory and a protagonist in thinking about the sustainability of his property, since he has the capacity to introduce innovations in productive processes, to promote genetic improvement, to create and be creative, to commit and work as a leader in the local community.